Morphoagronomic characterization of common bean genotypes (Caderno de Ciências Agrárias, 2024)
This work aimed to carry out morphoagronomic characterization of bean genotypes with aptitude for pod production. The experiment was carried out at the Federal University of Ceará, evaluating five bean genotypes in a randomized block design with five replications. Each experimental unit consisted of a bed with 9.6 m in length, with a spacing of 0.1 x 0.3 m. The morphoagronomic characterization of the genotypes was performed based on 15 characters. The quantitative descriptors were submitted to analysis of variance and the means were grouped using the Scott-Knott test. The dissimilarity between the genotypes was estimated based on the average Euclidean distance and the clustering performed by the UPGMA method. There were significant differences between the genotypes for all characters evaluated, except for the number of pods per plant. The Pronto Alívio genotype was the latest, however, it presented the highest yield of pods. The Pronto Alívio, Habichuela, Feijão Vagem do Panamá and Feijão-de-Metro genotypes stood out in terms of pod length and weight, in addition to presenting above-average productivity, which could be incorporated into crop improvement programs. Crossing between the varieties Feijão Vagem do Panamá and Pronto Alívio is recommended in order to obtain superior cultivars.